Paciente de sexo femenino de 23 años de edad que presenta cetoacidosis diabética - Parreño Cadena, Karem Denisse (2020)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia that leads the patient to suffer various comorbidities due to its damage at the micro and macrovascular level. It is a rapidly growing disease worldwide, according to the World Health Organization the number of figures has increased from 108 million in 1980 to 422 million in 2014. Diabetic Ketoacidosis develops rapidly within 24 hours presenting signs and symptoms such as polydipsia in conjunction with vomiting, dehydration and including diabetic coma. This case study is based on a 23-year-old female patient diagnosed with diabetes mellitus type mody 3, who is admitted to the hospital for presenting a clinical picture of decompensated diabetic ketoacidosis, characterized by respiratory distress, drowsiness, and altered state of consciousness. During the nutritional evaluation it was found that its Body Mass Index is within normal parameters, and that certain biochemical parameters are altered, according to the cut-off points of the World Health Organization. The objective of this case is to provide through a proper nutritional intervention a healthy eating plan of 1680 kcal / day –Improve the overall health and quality of life of the diabetic patient and eating habits avoiding complications in the future.